1983
DOI: 10.1038/301718a0
|View full text |Cite
|
Sign up to set email alerts
|

An inherited polymorphism in the human apolipoprotein A-I gene locus related to the development of atherosclerosis

Abstract: Epidemiological studies have identified elevated low density lipoprotein (LDL) and diminished high density lipoprotein (HDL) cholesterol levels as risk factors for coronary artery disease. The major protein component of HDL is apoprotein A-I (apo A-I), a polypeptide of 243 amino acids of known primary amino acid sequence. This apoprotein serves as a cofactor for the plasma lecithin-cholesterol acyltransferase (LCAT) enzyme responsible for the formation of most cholesteryl esters in plasma, and also promotes ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(51 citation statements)
references
References 20 publications
1
49
0
1
Order By: Relevance
“…When DNA was isolated from the white cells of the two probands, subjected to EcoRI digestion, and analyzed by Southern blot analysis by using an apo A-l gene probe, the probe hybridized to a unique 6.5 kb band in contrast to the normal 13 kb band. Similar experiments 103 in heterozygotes demonstrated the presence of both the normal 13 kb band and the abnormal 6.5 kb band. Recent data 104 has documented that the apo C-lll gene is approximately 2.6 kilobases downstream of the 3' end of the apo A-l gene, accounting for the observed genetic linkage.…”
Section: Familial Deficiency Of Apollpoprotelns A-l and C-lllsupporting
confidence: 68%
See 1 more Smart Citation
“…When DNA was isolated from the white cells of the two probands, subjected to EcoRI digestion, and analyzed by Southern blot analysis by using an apo A-l gene probe, the probe hybridized to a unique 6.5 kb band in contrast to the normal 13 kb band. Similar experiments 103 in heterozygotes demonstrated the presence of both the normal 13 kb band and the abnormal 6.5 kb band. Recent data 104 has documented that the apo C-lll gene is approximately 2.6 kilobases downstream of the 3' end of the apo A-l gene, accounting for the observed genetic linkage.…”
Section: Familial Deficiency Of Apollpoprotelns A-l and C-lllsupporting
confidence: 68%
“…103 ' 104 ' 140 ' 156 -158 A specific apo A-l gene abnormality has been reported based on the Southern blot analysis in familial deficiency of apolipoproteins A-l and C-lll. 1031104 No such abnormality exists in familial apolipoprotein A-l and C-lll deficiency or Tangier disease.…”
Section: Genetic Patternmentioning
confidence: 99%
“…In the case of Japanese, however, our data indicate that both the $2 and M2 alleles are common and not associated with coronary atherosclerosis. The apo CII1 Sst-I polymorphism arises from a C-G transversion in the 3'-non-coding region of the apo CIII gene (Karathanasis et al, 1983a). The apo A1 Msp-I polymorphism arises from the presence or absence of a Msp-I site in the third intron of the apo AI gene (Seilhamer et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The human apo AI and apo CIII genes are tightly linked and form a gene complex together with the apo AIV gene on the long arm of the chromosome 11 (Karathanasis, 1985). A mutation of the apo AI gene is associated with low plasma HDL and premature atherosclerosis (Karathanasis et al, 1983a(Karathanasis et al, , 1983b. In addition, restriction fragment length polymorphisms related to the apo AI and apo CIII genes have been reported to be associated with coronary atherosclerosis and familial hypoalphalipoproteinemia in Caucasians (Ferns et aI., 1985;Rees et al, 1985;Sidoli et al, 1985;Ferns and Galton, 1986;Ordovas et al, 1986;Buraczynska et al, 1986;Deeb et al, 1986;Acton et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that HDL cholesterol levels are negatively correlated with susceptibility to atherosclerosis and coronary artery disease [4,5]. A linkage between the human apoA-I and apolipoprotein C-I11 genes [6], as well as genetic polymorphisms associated with apoA-I and apoC-111 deficiency [7] or hypertriglyceridemia [8] have been recently reported.…”
mentioning
confidence: 99%